Activation of estrogen receptor beta signaling reduces stemness of glioma stem cells. (1st February 2021) - Sareddy, Gangadhara R.; Pratap, Uday P.; Venkata, Prabhakar Pitta; Zhou, Mei; Alejo, Salvador; Viswanadhapalli, Suryavathi; Tekmal, Rajeshwar R.; Brenner, Andrew J.; Vadlamudi, Ratna K.
Abstract: Glioblastoma (GBM) is the most common and deadliest tumor of the central nervous system. GBM has poor prognosis and glioma stem cells (GSCs) are implicated in tumor initiation and therapy resistance. Estrogen receptor β (ERβ) is expressed in GBM and exhibit tumor suppressive function. However, the role of ERβ in GSCs and the therapeutic potential of ERβ agonists on GSCs remain largely unknown. Here, we examined whether ERβ modulates GSCs stemness and tested the utility of two ERβ selective agonists (LY500307 and Liquiritigenin) to reduce the stemness of GSCs. The efficacy of ERβ agonists was examined on GSCs isolated from established and patient derived GBMs. Our results suggested that knockout of ERβ increased the proportion of CD133+ and SSEA+ positive GSCs and overexpression of ERβ reduced the proportion of GSCs in GBM cells. Overexpression of ERβ or treatment with ERβ agonists significantly inhibited the GSCs cell viability, neurosphere formation, self-renewal ability, induced the apoptosis and reduced expression of stemness markers in GSCs. RNA sequencing analysis revealed that ERβ agonist modulate pathways related to stemness, differentiation and apoptosis. Mechanistic studies showed that ERβ overexpression or agonist treatment reduced glutamate receptor signaling pathway and induced apoptotic pathways. In orthotopic models, ERβ overexpression or ERβ agonists treatment significantly reduced the GSCs mediated tumor growth and improved the mice overall survival. Immunohistochemical studies demonstrated that ERβ overexpression decreased SOX2 and GRM3 expression and increased expression of GFAP in tumors. These results suggest that ERβ activation could be a promising therapeutic strategy to eradicate GSCs. Abstract : This study results suggest that estrogen receptor beta (ERβ) activation could be a promising therapeutic strategy to eradicate glioma stem cells (GSCs). ERβ knockout in glioblastoma cells increased GSCs, while ERβ overexpression resulted in loss of GSCs. Overexpression of ERβ or treatment with ERβ agonists resulted in a reduction in GSCs cell viability, neurosphere formation, and self-renewal ability. Concurrently, the induction of apoptosis occurred following treatment with ERβ agonists. Mechanistic studies showed the reduction in stemness of GSCs is accomplished by transcriptional attenuation of the glutamate receptor pathway.